Distribution of Major Diseases of Banana Plants (Musa sp.) in Sofifi City, Oba Utara District, Tidore City - North Maluku - Rumahlewang, Wilhelmina; Uruilal, Costanza (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
Research on the distribution of diseases in banana plants has been conducted in Oba Utara District, Tidore City, North Maluku Province, focusing on Sofifi Village. One of the processed products in the form of crispy fried bananas is one of the favorites of the people in Balbar Village, Sofifi Village, Tidore Islands City, Oba Utara District, which is the location of this research. Banana cultivation in this village has not been carried out on a large scale. One of the obstacles to banana cultivation is the attack of pest organisms from the pathogenic group that causes disease. This study was conducted with the aim of determining the types of diseases in banana plants in Balbar village using a survey method (purposive sampling) in a planting area with more than 10 clumps as samples in this study. The results of the study obtained three (3) main types of diseases in banana plants in Balbar village, Sofifi sub-district, Tidore Islands City, namely: Colletotrichum musae which causes Coletotrichum leaf spots with a damage intensity (IK) of 66.67% (categorized as severe damage), Pseudocercospora musicola which causes cercospora leaf spots with an IK of 42.47% (category of moderate damage), and Cordana musae which causes cordana leaf spots with an IK of 19.35% (category of light damage).